Pengaruh Efektivitas Pendapatan Asli Daerah dan Pengelolaan Belanja Daerah terhadap Tingkat Kemandirian Keuangan Daerah (Studi Kasus pada Pemerintah Kabupaten/Kota di Provinsi Jawa Barat Tahun 2019-2023) - Rahmawati, Rahmawati; Hendaris, Raden Budi (Ekonomis: Journal of Economics and Business, 2025)
The purpose of this study is to analyze the influence of the effectiveness of Regional Original Revenue and the quality of regional expenditure management on the level of financial independence of regional governments. The study used data from various sources from 27 governments in West Java, both districts and cities, for the period 2019-2023. This study used multiple linear regression analysis. The results of this study revealed that simultaneously there was no significant influence between the variables of the effectiveness of Regional Original Revenue and Regional Expenditure Management on the Level of Regional Financial Independence. However, partially, only the variable of the Effectiveness of Regional Original Revenue had a positive and significant effect on the Level of Regional Financial Independence in Regency and City Governments in West Java Province in 2019-2023.